Care in Healthcare: Reflections on Theory and Practice - Joachim Boldt (Palgrave Macmillan, 2017)
This book examines the concept of care and care practices in healthcare from the interdisciplinary perspectives of continental philosophy, care ethics, the social sciences, and anthropology. Areas addressed include dementia care, midwifery, diabetes care, psychiatry, and reproductive medicine. Special attention is paid to ambivalences and tensions within both the concept of care and care practices. Contributions in the first section of the book explore phenomenological and hermeneutic approaches to care and reveal historical precursors to care ethics. Empirical case studies and reflections on care in institutionalised and standardised settings form the second section of the book. The concluding chapter, jointly written by many of the contributors, points at recurring challenges of understanding and practicing care that open up the field for further research and discussion. This collection will be of great value to scholars and practitioners of medicine, ethics, philosophy, social science and history.